Glycyl tRNA Synthetase (GARS) Gene Variant Causes Distal Hereditary Motor Neuropathy V - Peter Chung; Hope Northrup; Misbah Azmath; Ricardo A. Mosquera; Shade Moody; Aravind Yadav (Case Reports in Pediatrics)
Distal hereditary motor neuropathies (dHMN) are a rare heterogeneous group of inherited disorders specifically affecting the motor axons, leading to distal limb neurogenic muscular atrophy. The GARS gene has been identified as a causative gene responsible for clinical features of dHMN type V in families from different ethnic origins and backgrounds. We present the first cohort of family members of Nigerian descent with a novel heterozygous p.L272R variant on the GARS gene. We postulate that this variant is the cause of dHMN-V in this family, leading to variable phenotypical expressions that are earlier than reported in previous cases. The exact cause for the observed clinical heterogeneity within the family is unknown. One explanation is that there are modifier genes that affect the phenotype. These cases highlight the possibility of considering pathogenic variants in the GARS gene as a potential cause of early onset axonal polyneuropathy with atypical presentation.